Portrait of Josiah Willard Gibbs (Wilhelm Engelmann)
Portrait of Josiah Willard Gibbs (1839-1903). Gibbs, a Yale alumnus, was an American chemist and pioneer in the field of physical chemistry. Gibbs developed statistical mechanics and the concept of Gibbs free energy in thermodynamics.
Keywords: Gibbs, J. Willard (Josiah Willard), 1839-1903; Chemists; Portraits; Chemistry, Physical and theoretical; Meisenbach Riffarth & Company